Online Access to Doctors' Notes: Patient Concerns About Privacy - Vodicka, Elisabeth; Mejilla, Roanne; Leveille, Suzanne G; Ralston, James D; Darer, Jonathan D; Delbanco, Tom; Walker, Jan; Elmore, Joann G (JMIR Publications, 2013)
BackgroundOffering patients online access to medical records, including doctors' visit notes, holds considerable potential to improve care. However, patients may worry about loss of privacy when accessing personal health information through Internet-based patient portals. The OpenNotes study provided patients at three US health care institutions with online access to their primary care doctors' notes and then collected survey data about their experiences, including their concerns about privacy before and after participation in the intervention. ObjectiveTo identify patients' attitudes toward privacy when given electronic access to their medical records, including visit notes. MethodsThe design used a nested cohort study of patients surveyed at baseline and after a 1-year period during which they were invited to read their visit notes through secure patient portals. Participants consisted of 3874 primary care patients from Beth Israel Deaconess Medical Center (Boston, MA), Geisinger Health System (Danville, PA), and Harborview Medical Center (Seattle, WA) who completed surveys before and after the OpenNotes intervention. The measures were patient-reported levels of concern regarding privacy associated with online access to visit notes. Results32.91% of patients (1275/3874 respondents) reported concerns about privacy at baseline versus 36.63% (1419/3874 respondents) post-intervention. Baseline concerns were associated with non-white race/ethnicity and lower confidence in communicating with doctors, but were not associated with choosing to read notes or desire for continued online access post-intervention (nearly all patients with notes available chose to read them and wanted continued access). While the level of concern among most participants did not change during the intervention, 15.54% (602/3874 respondents, excluding participants who responded "don't know") reported more concern post-intervention, and 12.73% (493/3874 respondents, excluding participants who responded "don't know") reported less concern. ConclusionsWhen considering online access to visit notes, approximately one-third of patients had concerns about privacy at baseline and post-intervention. These perceptions did not deter participants from accessing their notes, suggesting that the benefits of online access to medical records may outweigh patients' perceived risks to privacy.